ANALYSIS OF THE STATE AND TRENDS OF DEVELOPMENT OF E-BUSINESS AND E-COMMERCE IN UKRAINE - MOZGOVA, Galyna; LIASHEVSKA, Viktoriia; ZAIKA, Olha; BILOKON, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study is devoted to the analysis of the state and trends of e-business and e-commerce in Ukraine. The data of Ukraine's positions among the other 37 countries of the European continent on the ratings of e-business infrastructure development and logistics are analyzed. Indices of the level of infrastructure development and logistics of e-business are considered, their characteristics are given, namely: Index of logistics efficiency; Index of ease of doing business; E-Government Development Index; Inclusive Internet index; Reliability indicator of the Universal Postal Union; Environmental efficiency index; Global Cyber Security Index. The main areas in which the Ministry of Finance performs tasks for the formation and implementation of public policy are identified: digitalization, digital development, digital economy, digital innovation, e-government and e-democracy, information society development; the field of development of digital skills and digital rights of citizens; open data, development of national electronic information resources and interoperability, development of broadband Internet and telecommunications infrastructure, e-commerce and business; sphere of providing electronic and administrative services; sphere of electronic trust services and electronic identification; sphere of development of the IT industry. The spheres in which the Ministry of Finance performs tasks on formation and realization of the state policy are defined. The directions of e-government development should be not only infrastructure development projects, but also educational and cultural projects to develop trust in obtaining public services via the Internet. The indicators of public access to the Internet are analyzed, so the domestic e-business has the prospect of development by connecting new consumers to the Internet. Online platforms are becoming a useful mechanism for small and medium enterprises, as they help to reach customers online without having to invest in a web store or branding.
Keywords: e-business; e-commerce; index; e-services